Ambient fine particulate matter disrupts hepatic circadian oscillation and lipid metabolism in a mouse model. (July 2020) - Li, Ran; Wang, Yixuan; Chen, Rucheng; Gu, Weijia; Zhang, Lu; Gu, Jinge; Wang, Ziyao; Liu, Ying; Sun, Qinghua; Zhang, Kezhong; Liu, Cuiqing
Abstract: Emerging evidence has shown that exposure to ambient fine particulate matter (PM2.5 ) is associated with hepatic lipid accumulation. However, the underlying mechanism is not fully characterized yet. Autonomous circadian clock in the liver plays a fundamental role in maintaining lipid metabolism homeostasis. In this study, we evaluated the effects of ambient PM2.5 exposure on the expression of hepatic circadian clock genes and expression rhythm of genes associated with lipid metabolism in mice liver. Male C57BL/6 mice were randomly assigned to ambient PM2.5 or filtered air for 10 weeks via a whole body exposure system. We found that the liver mass was reduced significantly at zeitgeber time (ZT) 8 in mice exposed to PM2.5 but not levels or circadian rhythm of hepatic triglycerides or free fatty acid (FFA). In addition, exposure to PM2.5 led to enhanced expression of bmal1 at ZT0/24, cry1 at ZT16 and rev-erbα at ZT4 and ZT8. Furthermore, the expression of pparα was enhanced in mice liver at ZT4 and ZT8 after PM2.5 exposure, with upregulation of pparα -mediated genes responsible for fatty acid transport and oxidation. Finally, the expression of rate-limiting enzymes for lipid synthesis was all significantly increased in the liver of PM2.5 exposed mice at ZT12. Therefore, the present study provides new perspectives for revealing the etiology of hepatic lipid metabolism abnormality from PM2.5 -induced circadian rhythm disorder. Graphical abstract: Image 1 Highlights: PM2.5 exposure altered the expression pattern or level of core circadian clock genes in mouse liver. PM2.5 exposure disrupted the rhythms of key transcription factors in hepatic lipid metabolism. PM2.5 exposure disrupted the rhythms of the key enzymes involved in hepatic lipid metabolism. Abstract : Perturbing hepatic circadian oscillations and lipid metabolism with ambient fine particulate matter exposure.